2016
DOI: 10.4168/aair.2016.8.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Pigment Epithelium-Derived Factor Inhibits Airway Inflammation and Remodeling in Chronic OVA-Induced Mice via VEGF Suppression

Abstract: PurposePigment epithelium-derived factor (PEDF) is a recently discovered antiangiogenesis protein. PEDF possesses powerful anti-inflammatory, antioxidative, antiangiogenic, and antifibrosis properties. It has been reported that PEDF can regulate vascular endothelial growth factor (VEGF) expression. This study aimed to evaluate whether recombinant PEDF protein could attenuate allergic airway inflammation and airway remodeling via the negative regulation of VEGF using a murine model of chronic ovalbumin (OVA)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…IL-1β is involved in chronic inflammation, ECM metabolism, and tissue remodeling in a variety of tissues and organs [14,15]. In present study, we clearly showed that IL-1β induced myofibroblast differentiation, ECM production, migration, and collagen contraction in nasal fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
“…IL-1β is involved in chronic inflammation, ECM metabolism, and tissue remodeling in a variety of tissues and organs [14,15]. In present study, we clearly showed that IL-1β induced myofibroblast differentiation, ECM production, migration, and collagen contraction in nasal fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
“…well known that VEGF plays an important role in airway remodeling, and several studies have shown that VEGF expression is significantly increased in the serum of asthmatic and/or COPD patients. 29 However, based on the result of our study, a negative correlation between serum VEGF-A and FEV1/FVC was observed, which might be possibly related to emphysema observed in ACOS in asthmatic patients. It had been clearly reported that the concentration of VEGFA and its receptor VEGFR2 significantly decreased in emphysema.…”
Section: Discussionmentioning
confidence: 46%
“…9A and B ). In addition, the expression level of VEGF, which is a stimulator of angiogenesis and structural changes in asthma ( 23 ), was significantly decreased in the OVA + SEAC-treated groups compared with the OVA + vehicle-treated group ( Fig. 9C ).…”
Section: Resultsmentioning
confidence: 94%